Evaluation of Environmental Health Indicators of Halva and Tahini Production Centers in Ardakan, Yazd - Mohammad Taghi Ghaneian; Jalal Sadeghi zadeh; Mahboobeh Matoob; Mohammad Hassan Ehrampoosh; Bahador Hajimohammadi; Hossein Fallahzadeh; Arefe Dehghani tafti; Mahboobeh Dehvari (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Attention to food safety and health at all stages from production to consumption is inevitable. Inappropriate sanitary status of the food production, distribution and supply centers caused food-borne diseases. The aim of this study was to evaluate the environmental health indicators of halva and tahini production centers in the city of Ardakan in 2013. Materials & Methods: This is a descriptive, cross- sectional study. For data collection, the checklist were prepared consisting 5 part raw materials store, production processing halls, packaging halls, product store and bathrooms according to regulations form of article 13, law of edible, drinking, cosmetics materials of the department health, treatment and medical education with questions in different fields such as health card status, observance personal hygiene, status production centers structural, observance the criteria about the number of bathrooms, showers and toilets, wastewater disposal method and observance health principles in the halva and tahini production centers that during a inspection from 16 production centers were completed in the winter. Final, obtained data analyzed by SPSS, version 18 and χ2 test. Results: Generally, 75% production centers had favorable hygienic status and 25% had slightly favorable hygienic status. According to obtained results, hygienic status of production centers had relatively favorable and favorable conditions and only in January and February in 31.3% and 18.8% processing hall and 12.5% product store was in a very favorable hygienic status. The results showed that in terms of environmental health status, 62.5% production centers in raw materials store part, 66.66% in production processing hall, 20.83% in packaging hall, 60.41% in product store and 37.5% in bathrooms had favorable status. Based on the results, hygienic status of bathrooms and processing hall achieved lowest and highest score, respectively. Statistical analysis showed that between hygienic status and production rate (p=0.411) there is no significant relationship. Conclusion: The results of this study indicate that the halva and tahini production centers of Ardakan city in terms of environmental health indicators had slightly favorable status to favorable and none of the production centers had not very favorable conditions. The results of this study can be used to improve health status of halva and tahini production centers.